Aberrant Methylation and Immune Microenvironment Are Associated With Overexpressed Fibronectin 1: A Diagnostic and Prognostic Target in Head and Neck Squamous Cell Carcinoma - Sheng, Surui; Guo, Bing; Wang, Zhentao; Zhang, Zhihua; Zhou, Jieyu; Huo, Zirong (Frontiers in Molecular Biosciences, 2021)
Background: Fibronectin 1 (FN1) is involved in cell adhesion and migration processes such as metastasis, wound healing, embryogenesis, blood coagulation and host defense. However, the role of FN1 in the diagnosis and prognosis of head and neck squamous cell carcinoma (HNSCC) is far from understood. Methods: FN1 expression profiles and clinical parameters from multiple HNSCC datasets were applied to evaluated the association between FN1 expression and HNSCC survival. We also identified FN1 expression in the mRNA and protein levels in 20 pairs of clinical samples by quantitative polymerase chain reaction (qPCR) and immunohistochemistry. Receiver operator characteristic (ROC) analysis was used to demonstrate the potential prognostic value of FN1 in HNSCC. Aberrant methylation PPI network were established using multiple bioinformatic tools based on TCGA database. The immune microenvironment and levels of immune checkpoints were investigated between groups with higher and lower FN1 expression. Results: FN1 was significantly upregulated in HNSCC compared with para-carcinoma tissues on the basis of TCGA database, as well as our clinical samples. Univariate and multivariate cox regression analysis revealed that FN1 could be an independent indicator for prognosis of HNSCC. GO enrichment and KEGG pathway analysis demonstrated that cell adhesion, focal adhesion and PI3K-Akt signaling pathway might be involved in the potential mechanisms of FN1’s prognostic performance in HNSCC. Methylation of FN1 was also higher and closely associated with poorer survival in HNSCC. In addition, FN1 expression was positively correlated to 3 DNA methyltransferases (DNMT1, DNMT3A, DNMT3B). Furthermore, FN1 was positively associated with CD4+ T cells, endothelial cells, macrophages, and NK cells, and negatively correlated with CD8+ T cells. Conclusion: FN1 might be an independent prognostic biomarker for HNSCC patients. Hypermethylation, the aberrant proportions of immune cells, and PI3K/Akt signaling pathway might involve to the mechanism of FN1’s oncogene role in HNSCC.